Escolarização no norte do Espírito Santo início do Século XX : das escolas isoladas aos grupos escolares - Alencar, Ingrid Regis de Freitas Schmitz de (2016)
The work investigates the expansion of the Elementary School held in the north of Espírito Santo State, from 1908 to 1930, and the ramifications of the republican speeches regarding the educational field, in circulation in that period, concerning the expansion process of the primary schooling in the north of the state. It uses as theoretical referential the comprehension, treatment and work with the sources proposed by Carlo Ginzburg, Marc Bloch and Michel de Certeau. Such authors' ideas contributed for the education history approaches in the north of the State from a micro-analytical approach that proposes the variation of scales. Messages from the government, instruction reports and inspections, separate official documents, decrees and regulations about the instruction in this period, photographs, newspaper articles and books, dissertations and articles about the history of pronounced districts compose the documental corpus of the research that is considered to be the teaching expansion in the north of Espírito Santo mainly carried out through the work of isolated school Teachers, whose physical and structural conditions are not in conformity with the programmed republican school speech. The constructions intended to be school groups in that region reveal the weakness and lack of the institution, which materiality has been only affirmed in the political discourse. This research considers approaches and gaps between the districts of Colatina and São Mateus, indicating that the elementary school expansion process presents singularities in both cases. It is about a contribution for the knowledge of the education history in the north of Espírito Santo.